Notice of a Sculptured Stone on the Farm of Auchrynie, Parish of Old Deer, Aberdeenshire - Murray, Alexander (Proceedings of the Society of Antiquaries of Scotland, 1865)
[The journal notes that this paper was delivered by Alexander Murray, but the content of the communication was not recorded.]